1976
DOI: 10.1111/j.1346-8138.1976.tb00971.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pattern of Vitiligo Amongst Indians

Abstract: Vitiligo incidence in the series was 14 per thousand. The affliction of the younger subjects was frequent, the mean value of age at onset being 24.25 years. Both the sexes were affected and there was no significant difference between the two. The duration of the disease had wide variations, majority reporting in the course of one year. The emotional undertones and the ocurrence of the disease amongst family links were observed as provocating factors in some cases. Ivory white macules associated sometimes with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
6

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 6 publications
1
10
0
6
Order By: Relevance
“…Our study was limited by its short duration which did not allow us to evaluate the lesions' outcome on the long run. The 1.2% frequency is close to the one registered by Sehgal et al in India [5] and the frequency of 1 to 2% reported worldwide [6]. The female predominance was also observed by Kar [7] who noted 51.6% of women against 48.35% of men.…”
Section: Discussionsupporting
confidence: 81%
“…Our study was limited by its short duration which did not allow us to evaluate the lesions' outcome on the long run. The 1.2% frequency is close to the one registered by Sehgal et al in India [5] and the frequency of 1 to 2% reported worldwide [6]. The female predominance was also observed by Kar [7] who noted 51.6% of women against 48.35% of men.…”
Section: Discussionsupporting
confidence: 81%
“…16,17 The mean age of onset is earlier in those with a positive family history, 2,18 which ranges from 7.7% to more than 50%. 2,17,[19][20][21][22][23] Vitiligo is significantly more prevalent in young women ( # 30 years of age) than young men. 1,13,24,25 The peak in females occurs in the first decade of life.…”
Section: Learning Objectivesmentioning
confidence: 99%
“…1 Vitiligo is commonly associated with systemic autoimmune conditions, including hypothyroidism and hyperthyroidism, 2 diabetes mellitus, 3 and Sjögren's syndrome. 4 Many autoimmune conditions have been associated with reduced vitamin D levels, including rheumatoid arthritis, diabetes mellitus, and multiple sclerosis.…”
Section: Introductionmentioning
confidence: 99%